Зарубіжний досвід надання адміністративних послуг органами публічної влади та можливості його використання в Україні - Тихонова, Д. С.; Tykhonova, D. S. (Право і безпека. - 2014. - № 4 (55). - С. 70-75, 2014)
Розглянуто досвід зарубіжних країн (Німеччини, Нідерландів, Польщі, Бразилії та Канади) у сфері організації системи надання адміністративних послуг органами публічної влади. Установлено, що обслуговування населення з надання адміністративних послуг органами публічної влади здійснюється спеціальними установами – «універсамами послуг» (Німеччина, Нідерланди, Польща, Канада), центрами обслуговування населення (Бразилія). Сформульовано пропозиції, які можуть бути використані як рекомендації для розвитку вітчизняної системи адміністративних послуг.

The experience of foreign countries (Germany, the Netherlands, Poland, Brazil and Canada) in the sphere of organizing the system of providing administrative services by public authorities is studied in the paper. It is established that the public services in the sphere of providing administrative services by public authorities are carried out by special institutions like centers of providing services (Germany, the Netherlands, Poland, Canada), centers of service population (Brazil). It was found out that provision of administrative services in these countries is realized in accordance with standards, which define the components of services’ quality. They are availability, timeliness, priority of needs of citizens and others. These components define priorities of specialized agencies’ activity, creating favorable conditions of receiving services by the public. It is established that all these countries have a system of e-government, which provides free access to the so-called single portals of the state (administrative) services, which contain information about the list of conditions, the procedure of receiving administrative services. Propositions that can be used as guidelines for the development of national system of administrative services are formulated.

Рассмотрен опыт зарубежных стран (Германии, Нидерландов, Польши, Бразилии и Канады) в сфере организации системы предоставления административных услуг органами публичной власти. Установлено, что обслуживание населения по предоставлению административных услуг органами публичной власти осуществляется специальными учреждениями – «универсамами услуг» (Германия, Нидерланды, Польша, Канада), центрами обслуживания населения (Бразилия). Сформулированы предложения, которые могут быть использованы в качестве рекомендаций для развития отечественной системы административных услуг.
Foreign experience of providing administrative services by public authorities and possibilities of its usage in Ukraine
Зарубежный опыт предоставления административных услуг органами публичной власти и возможности его использования в Украине
Keywords: зарубіжний досвід; адміністративні послуги; органи публічної влади; «універсами послуг»; система адміністративних послуг; foreign experience; administrative services; public authorities; centers of providing services; system of administrative services; зарубежный опыт; административные услуги; органы публичной власти; «универсамы услуг»; система административных услуг